Tick-borne pathogens in the blood of wild and domestic ungulates in South Africa: interplay of game and livestock - Berggoetz, M.; Schmid, M.; Ston, D.; Wyss, V.; Chevillon, C.; Pretorius, A.M.; Gern, L. (Elsevier GmbH: Ticks and Tick-borne Diseases 5, 2014)
We screened for tick-borne pathogens blood samples from 181 wild and domestic ungulates belonging to 18 host species in 4 South African Provinces. Polymerase chain reaction followed by reverse line blotting and sequencing allowed detecting 16 tick-borne pathogen species belonging to the genera Babesia, Theileria, Anaplasma, and Ehrlichia. Ten pathogen species were involved in 29 new host–pathogen combinations. Most infections (77.9%) involved more than one pathogen species. Principal component analysis (PCA) assigned the 163 infections, identified to species level, to 4 groups. Three groups were associated with sheep, cattle, and horse and their respective wild counterparts. Each group was characterised by high homogeneity in pathogen assemblage and host phylogenetic status. These groups characterised the most privileged transmission routes between and among wild and domestic ungulates. The 4th group showed high heterogeneity in pathogen assemblage and host phylogenetic status. This group seems to indicate frequent spill over events in impala of pathogens that usually circulate among cattle- or sheep-related species. Within 6 localities, we sampled an equal number of wild and domestic animals (n = 128). On this dataset once having controlled for the significant variation among localities, the infection prevalence and intensity of infection did not differ significantly between wild and domestic hosts. This suggests that both animal types, domestic and wild hosts, could act as evenly efficient sources of infection for themselves and for each other. Overall, this study shed new light on the pathogen circulation naturally achieved at the interplay between wild and domestic ungulates.
Published Article
Keywords: African wildlife; Anaplasma; Babesia; Coinfections; Ehrlichia; Livestock; Theileria; Tick-borne pathogens